Fuzzy Zagreb Index and Its Application in Financial Interconnection Networks - Kale, Mahesh; S., Minirani (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2020)
In contrast to conventional models, fuzzy graphs offer an enhanced level of precision and adaptability for systems. These graphs provide a numerical representation of a molecule's structural graph through topological indices. In the realm of graph theory, numerous topological indices can be applied to the domain of fuzzy graphs. This paper elucidates the utilization of fuzzy graph theory indices within interconnection networks. The scope of this analysis encompasses the derivation of analytical results for the fuzzy Zagreb index and its practical applications in interconnecting companies within the field of financial mathematics. Additionally, we leverage fuzzy graph modeling to investigate a significant approach to designing efficient investment strategies, harnessing the power of the fuzzy Zagreb index as a key tool in this endeavor.